High Level of Nonsynonymous Changes in Common Bean Suggests That Selection under Domestication Increased Functional Diversity at Target Traits - Bitocchi, Elena; Rau, Domenico; Benazzo, Andrea; Bellucci, Elisa; Goretti, Daniela; Biagetti, Eleonora; Panziera, Alex; Laidò, Giovanni; Rodriguez, Monica; Gioia, Tania; Attene, Giovanna; McClean, Phillip; et al. (Frontiers in Plant Science, 2017)
Crop species have been deeply affected by the domestication process, and there have been many efforts to identify selection signatures at the genome level. This knowledge will help geneticists to better understand the evolution of organisms, and at the same time, help breeders to implement successful breeding strategies. Here, we focused on domestication in the Mesoamerican gene pool of Phaseolus vulgaris by sequencing 49 gene fragments from a sample of 45 P. vulgaris wild and domesticated accessions, and as controls, two accessions each of the closely related species P. coccineus and P. dumosus. An excess of nonsynonymous mutations within the domesticated germplasm was found. Our data suggest that the cost of domestication alone cannot explain fully this finding. Indeed, the significantly higher frequency of polymorphisms in the coding regions observed only in the domesticated plants (compared to noncoding regions), the fact that these mutations were mostly nonsynonymous and appear to be recently derived mutations, and the investigations into the functions of their relative genes (responses to biotic and abiotic stresses), support a scenario that involves new functional mutations selected for adaptation during domestication. Moreover, consistent with this hypothesis, selection analysis and the possibility to compare data obtained for the same genes in different studies of varying sizes, data types, and methodologies allowed us to identify four genes that were strongly selected during domestication. Each selection candidate is involved in plant resistance/ tolerance to abiotic stresses, such as heat, drought, and salinity. Overall, our study suggests that domestication acted to increase functional diversity at target loci, which probably controlled traits related to expansion and adaptation to new agro-ecological growing conditions.